Development of e-books integrated with the Qur’an to support learning in the nutrition and health course within the biology education program at the university - Ainul Uyuni Taufiq; Hamansah Hamansah; Nurul Hasfika Sari; Nur Alamsyah (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2024)
The education digitalization era is growing rapidly, and integrating information technology with religious values is becoming increasingly important, especially in providing relevant and holistic learning resources. This research aims to create an integrated e-book with the Al-Quran to support learning in nutrition and health courses in the Biology Education Study Program at UIN Alauddin Makassar, which is valid, practical, and effective. This research uses research and development with the ADDIE development model. Development products are tested through validity, practicality, and effectiveness tests. The research subjects were validation experts (validators), practitioners (course lecturers), and sixth-semester students taking the nutrition and health course in the Biology Education Study Program. The research instruments are media validation sheets, response questionnaires, and response questionnaires, as well as learning outcomes test items. The research results showed that the media developed had a validity level of 3.86 (very suitable) and a practicality level based on response assessment, namely 3.61 (highly practical). The learning outcomes test has a percentage level of effectiveness with a percentage of 20% in the very effective category, 68% in the effective category, and 12% in the quite effective category. Classically, 88% reached the minimum value for the effective category. Based on the findings of this study, the development of e-books integrated with religious values is recommended to be optimized in dissemination, similar development, and application.Abstrak. Era digitalisasi pendidikan yang berkembang pesat, dan integrasi antara teknologi informasi dengan nilai-nilai keagamaan menjadi semakin penting, terutama dalam konteks penyediaan sumber belajar yang relevan dan holistik. Penelitian ini bertujuan untuk e-book terintegrasi Al-Quran untuk Menunjang Pembelajaran pada Mata Kuliah Gizi dan Kesehatan Prodi Pendidikan Biologi UIN Alauddin Makassar yang bersifat valid, praktis, dan efektif. Penelitian ini menggunakan jenis penelitian dan pengembangan dengan model pengembangan ADDIE. Produk pengembangan diuji melalui uji validitas, uji kepraktisan dan uji keefektifan. Subjek penelitian adalah ahli validasi (validator), praktisi (dosen mata kuliah), dan mahasiswa semester enam yang memprogramkan mata kuliah Gizi dan Kesehatan pada Progtam Studi Pendidikan Biologi. Instrumen penelitian berupa lembar validasi media, angket respon dan angket respon, serta butir-butir tes hasil belajar. Hasil penelitian menunjukkan bahwa media yang dikembangkan memiliki tingkat validitas yaitu 3.86 (sangat layak), tingkat kepraktisan berdasarkan penilaian respon yaitu 3,61 (sangat praktis). Tes hasil belajar memiliki persentase tingkat kefektifan dengan persentase 20% kategori sangat efektif, 68% kategori efektif, dan 12% kategori cukup efektif. Secara klasikal 88% mencapai nilai minimum untuk kategori efektif. Berdasarkan temuan dari penelitian ini, pengembangan e-book terintegrasi nilai-nilai keagamaan direkomendasikan untuk dioptimalkan dalam penyebarluasan, pengembangan serupa, maupun penerapannya.